Benefits that Death Does Not Part: the Promise of Postbiotics for Bone Health - Ribeiro, Jaqueline Lemes [UNESP]; Santos, Thaís Aguiar [UNESP]; Anbinder, Ana Lia [UNESP] (Springer Nature, 2025)
Postmenopausal osteoporosis (PMO) is a widespread global health concern characterized by hormone deficiency. The existing therapies for PMO often have undesirable side effects, necessitating the development of safe and effective alternative treatments. Probiotics, which are live microorganisms that promote the host health, have been explored as a potential solution. However, concerns have been raised regarding their use, particularly the safety when administered to vulnerable populations (e.g., elderly and immunodeficient individuals). Additionally, the industrial processing and storage of probiotic products present technological challenges that can compromise their viability. To address these drawbacks, the focus has shifted towards non-viable probiotics known as postbiotics. Postbiotics are defined as inactivated (dead) microbial cells or their byproducts that provide health benefits to consumers. They exhibit immunomodulatory properties and demonstrate antagonistic effects against pathogens. Furthermore, postbiotics offer enhanced safety, technological advantages, and practical benefits. By leveraging these unique attributes, postbiotics present a promising opportunity to introduce novel therapies that are safer and more stable. This review provides an overview of key considerations surrounding postbiotics, summarizes recent literature on their application in PMO, and underscores the urgent need for further randomized clinical trials. These trials should evaluate the safety, efficacy, and mechanisms of action of postbiotic products to support regulatory decision-making processes.